(untitled) (Research, Society and Development, 2025)
Colic is a common and dangerous condition that causes abdominal discomfort in horses. Its resolution can be clinical or surgical, caused by a range of possible abnormalities. One such alteration is intussusception, where one segment of the intestine (the intussusceptum) is enveloped by an adjacent aboral segment (the intussuscipiens). The progression of this condition leads to ischemia and necrosis of the involved intestinal loops, underscoring the importance of early diagnosis and intervention. When the ileum is involved and complete resection is necessary, jejunocecostomy is the recommended surgical technique, leaving a remnant ileal stump and creating a new ileocecal valve. This work aims to report the case of a 6-year-old Crioulo mare, which was presumptively diagnosed with acute intussusception through clinical and ultrasonographic findings (bull’s eye formation), confirming the suspicion during exploratory celiotomy that was promptly performed. The anastomosis of the cecum to the resected end of the jejunum was accomplished using gastrointestinal staplers. The surgery was successful and the patient was discharged from the hospital without complications 7 days post-procedure, subsequently returning to its activities satisfactorily. This report emphasizes the impact of the time between presentation and resolution on the prognosis of patients with colic, due to the progressive local and systemic damages caused by this syndrome.